Two Decades of Bibliometric Research in Indonesia - Kamaludin (Mr.) Kamaludin; Abdurakhman Prasetyadi (THE LIGHT : Journal of Librarianship and Information Science, 2023)
Bibliometric research in Indonesia is essential to do for exploring trends and understanding the knowledge base of bibliometric research from the perspective of globally indexed publications. Bibliometric studies have been applied mainly to scientific fields of activity, mostly based on metadata elements such as author, title, subject, citation, etc., related to scientific publications in a discipline. However, no study explicitly discusses the development of bibliometric research in Indonesia based on globally indexed publications. This study aims to identify 1) the growth of bibliometric research in Indonesia, 2) the performance of scientific agencies in publishing bibliometric research in Indonesia, and 3) the science mapping of bibliometric research in Indonesia. This study used data and graphical quantification methods to help researchers understand the future progress and trends of bibliometric research in Indonesia. The study results show that within two decades, there have been 167 relevant documents published and globally indexed in this field. The 167 documents were then analyzed and interpreted using bibliometric techniques: performance analysis and science mapping. The performance analysis results show that bibliometric publications in Indonesia continue to increase from one publication in 2001 to 85 documents in 2022. The most popular categories studied with bibliometrics are Environmental science and Engineering. The analysis results also show the productivity of each scientific actor, including writers, institutions, and countries. The conclusion showed four significant clusters in bibliometric research in Indonesia: the Chemical science cluster, Bibliometric analysis and literature review, food safety, and top Indonesian universities.